Modelagem computacional no movimento de partículas em suspensão no estuário do rio Pará - ALMEIDA, Lucas Oliveira de (2020)
This research investigated the movement of suspended particles in the Pará River estuary, one of the largest rivers in northern Brazil, through computer modeling. Using the Pará River estuary and a portion of the continental shelf as a domain, the hydrodynamic modeling was made using the Delft 3d flow program for flexible mesh creation and the drogue functions for simulating suspended particles movements. Simulations were performed for two different river discharge periods, one low river discharge (2200 m3 / s) and another high river discharge (12200 m3 / s). Both scenarios were completed with 30 days of simulation, using a 5 minute time step, yielding one hour results. Model calibration was performed by comparing computational modeling data and in situ data. Four virtual derivators were launched for simulation or suspended particle motion in the fluid. With derivator number 04 being launched near fundeadouro de Mosqueiro approximately 85 km from the mouth of the estuary, number 1 approximately 50 km from the mouth, the second approximately 13 km from Cabo do Maguari (outside) and number 3 at the central outside a mouth of the estuary (20 km from the island of Guarás). The results show that, in periods of low river discharge, there is a tendency to move northwest, with greater difficulty of movement for those located in the innermost region of the estuary to reach the ocean. In high river discharge, it is easier for the particles on inner regions to reach the ocean with a slight eastward trend (movement towards the salgado paraense)